THE INFLUENCE OF PERFORMANCE ALLOWANCES AND LEADERSHIP STYLE ON EMPLOYEE PRODUCTIVITY AT PT. BANK EKONOMI RAKYAT SYARIAH (BPRS) NIAGA MADANI KOTA MAKASSAR - Nadia, Nadia; Andi Mappatompo; Sri Andayaningsih (CV. AFDIFAL MAJU BERKAH, 2024)
This research is a quantitative description type research that aims to know and analyze the effect of performance allowances and leadership styles on employee work productivity at PT. Bank Perekonomian Rakyat Syriah (BPRS) Niaga Madani Makassar City. The method used in this study amounted to 32 respondents with the analysis method used was multiple linear regression analysis which was processed through the help of Statistical Product and Service Solution software (SPSS0 Version 27. The results of this study can be concluded that the performance allowance variable and leadership style have a positive and significant influence on employee work productivity at PT. Bank Perekonomian Rakyat Syariah (BPRS) Niaga Madani Kota Makassar.